"She had brought her thighs to her belly, opened her legs like a book”. Rewritings of Apollinaire in “South of the Eyelids” by Enrique Vila-Matas - Blesa, Túa (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
This article focuses on the episodes of violence and sex in Enrique Vila-Matas's novel South of the Eyelids (1980), issues that make this novel a unique text in his entire body of work. Episodes that are another example of the poetics of intertextuality so characteristic of Vila-Matas’ work, which are appropriations of Guillaume Apollinaire’s novel The Eleven Thousand Dicks.
Keywords: Enrique Vila-Matas; South of the Eyelids; sex; violence; intertextuality; Guillaume Apollinaire's The Thousand Eleven Dicks